Diagnosis, prevalence, and clinical impact of sarcopenia in COPD: a systematic review and meta‐analysis. Issue 5 (30th August 2020) - Sepúlveda‐Loyola, Walter; Osadnik, Christian; Phu, Steven; Morita, Andrea A.; Duque, Gustavo; Probst, Vanessa S.
Abstract: Sarcopenia prevalence and its clinical impact are reportedly variable in chronic obstructive pulmonary disease (COPD) due partly to definition criteria. This review aimed to identify the criteria used to diagnose sarcopenia and the prevalence and impact of sarcopenia on health outcomes in people with COPD. This review was registered in PROSPERO (CRD42018092576). Five electronic databases were searched to August 2018 to identify studies related to sarcopenia and COPD. Study quality was assessed using validated instruments matched to study designs. Sarcopenia prevalence was determined using authors' definitions. Comparisons were made between people who did and did not have sarcopenia for pulmonary function, exercise capacity, quality of life, muscle strength, gait speed, physical activity levels, inflammation/oxidative stress, and mortality. Twenty‐three studies (70% cross‐sectional) from Europe (10), Asia (9), and North and South America (4) involving 9637 participants aged ≥40 years were included (69.5% men). Sarcopenia criteria were typically concordant with recommendations of hEuropean and Asian consensus bodies. Overall sarcopenia prevalence varied from 15.5% [95% confidence interval (CI) 11.8–19.1; combined muscle mass, strength, and/or physical performance criteria] to 34% (95%CI 20.6–47.3; muscle mass criteria alone) ( P  = 0.009 between subgroups) and was greater in people with more severe [37.6% (95%CI 24.8–50.4)] versus less severe [19.1% (95%CI 10.2–28.0)] lung disease ( P  = 0.020), but similar between men [41.0% (95%CI 26.2–55.9%)] and women [31.9% (95%CI 7.0–56.8%)] ( P  = 0.538). People with sarcopenia had lower predicted forced expiratory volume in the first second (mean difference −7.1%; 95%CI −9.0 to −5.1%) and poorer exercise tolerance (standardized mean difference −0.8; 95%CI −1.4 to −0.2) and quality of life (standardized mean difference 0.26; 95%CI 0.2–0.4) compared with those who did not ( P  < 0.001 for all). No clear relationship was observed between sarcopenia and inflammatory or oxidative stress biomarkers. Incident mortality was unreported in the literature. Sarcopenia is prevalent in a significant proportion of people with COPD and negatively impacts upon important clinical outcomes. Opportunities exist to optimize its early detection and management and to evaluate its impact on mortality in this patient group.